« Un épagneul, une femme et un noyer, plus nous les battons, meilleurs ils sont » : Frances Power Cobbe, la féminité et l’altérité - Émilie Dardenne (Revue LISA)
Frances Power Cobbe was a remarkable Victorian and a very assertive woman, who was praised for both her astute feminist mind and her tenacious fight against animal experiments. She utterly disapproved of women being ranked as creatures whose whole existence depended on their relationship with another individual. She deplored their “wretched proverbial similarity to spaniels and walnut-trees”. In her writings, she tackled the theme of violence, especially that committed within the home by malicious husbands and she took strong exception to “the notion that a man’s wife is his PROPERTY”, because of the stigma attached to such a belief and because it made women—as well as animals—morally inferior to men.The following article provides an insight into Frances Power Cobbe’s perspective on domestic violence and her in-depth exploration of the concepts of femininity and otherness. It begins by explaining how the authoress of “Wife Torture in England” became the spokeswoman of beaten wives and it goes on to study her vision of femininity as conveyed through her discussion of violence, cruelty, appropriation, otherness and the fate of animals. The article concludes by trying to shed light on the image of femininity that Cobbe wishes to extol.